Komunikasi Lingkungan pada Bank Sampah di Kota Bandung dan Kabupaten Bandung: Sebuah Studi Komparatif - Haqqi Annazilly, Muhammad; Dirgantara, Pradipta (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
The aim of this research is to determine environmental communication in the Bersinar Waste Bank in Bandung Regency and the DLH Main Waste Bank in Bandung through a comparative study. The research method used is a qualitative method with a case study approach. The choice of this method is based on facts in the field. The research results show that the waste management carried out by the Bandung City DLH Waste Bank and the Bersinar Bandung Regency Waste Bank is quite good, starting from the procedures for delivering messages, the completeness of the platforms used and the programs created. Bandung City DLH Waste Bank and Bandung Regency Bersinar Waste Bank must continue to make positive improvisations to reduce the waste problem which continues to be a major problem in Bandung City and Regency. The positive impact that can be seen from the environmental communication process carried out by the two Waste Banks is that people are increasingly concerned about protecting the environment by managing, sorting and saving waste at the Waste Bank. This impact can be seen from the public's response which can interpret the messages conveyed during socialization and conveying information via social media.